NALYSIS OF HERBARIUM SPECIMENS OF ASTRAGALUS SIEVERSIANUS STORED IN THE NATIONAL HERBARIUM (TASH) OF UZBEKISTAN FROM THE FLORA OF THE FERGANA VALLEY - Umaraliyeva Shodiyona Farhodjon girl (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ANNOTATION: This article presents a morphological analysis of Astragalus sieversianus Pall., based on 25 herbarium specimens collected from the Fergana Valley and preserved at the National Herbarium of Uzbekistan (TASH) between 1938 and 2018. Key traits including leaf morphology, floral structures, fruit shape, and seed characteristics were examined. Results show a shift in distribution from lowlands to foothill regions in recent decades, possibly due to anthropogenic impact and environmental changes. Some morphological variability suggests the existence of local ecotypes. The study highlights the importance of herbarium data in species monitoring and indicates the need for further molecular research for conservation planning.